Quest for the queen - Abbott, Tony.; Jessell, Tim (New York : Scholastic, 2000)
Princess Keeah wants to win the Quest, but Eric, Neal, and Julie must make sure that everyone else is playing fairly.
"A Little Apple paperback."
4.7
3-6
Keywords: Magic -- Fiction; Fantasy; Magic -- Fiction; Fantasy fiction